Communicating the Climate Crisis: Stories in the Classroom - Prajnč Kacijan, Nastja; Leva, Bernarda; Majcenovič Kline, Barbara; Hazemali, David; Mohar, Tjaša; Plemenitaš, Katja; Onič, Tomaž; Hempkin, Kirsten (Komuniciranje okoljske krize, 2025)
As the climate crisis escalates, educators find themselves frequently having to engage with this issue in a classroom context. A significant contribution that educators, especially language teachers, can make is connected to communicating about environmental questions and helping learners develop the critical skills and competences to engage with such questions fully. In this contribution, we present a series of tasks drawing upon the medium of stories – both fiction and non-fiction, for younger and older learners – which are designed to develop a number of key competences: enhance vocabulary in English relating to climate issues; develop awareness of the key themes regarding these issues; increase learners' critical thinking (regarding the use of language specifically) concerning information available on climate change and related issues.